The Safety of Neuromuscular Blockade Reversal in Patients With Cardiac Transplantation. Issue 12 (December 2016) - Barbara, David W.; Christensen, Jon M.; Mauermann, William J.; Dearani, Joseph A.; Hyder, Joseph A.
Abstract : Background: Neuromuscular blockade (NMB) reversal with neostigmine and glycopyrrolate has been reported to cause cardiac arrest in patients with a history of cardiac transplantation. The purpose of this study was to examine the safety of NMB reversal with acetylcholinesterase inhibitors and muscarinic anticholinergics in these patients. Methods: We queried the medical records of a large tertiary referral center for patients with a history of prior heart transplantation who underwent anesthesia including receipt of NMB reversal. Patient records were reviewed to investigate maximal decrease in heart rate (HR) after NMB reversal and incidence of death and cardiac arrest. Results: Seventy-seven heart transplant patients underwent 118 subsequent anesthetics during which they received neostigmine and glycopyrrolate for NMB reversal. No patients had active pacemakers at the time of their anesthetics. Mean time from heart transplantation to NMB reversal was 2.9 ± 3.2 (median, 1.9; range, 0.01– 12.5) years. After NMB reversal, no patients received atropine or epinephrine, suffered cardiac arrest, or died within 30 days. Mean HR decrease, defined as the difference between the HR immediately before NMB reversal and the lowest HR within 5 minutes thereafter, after NMB reversal was 0.5 ± 3.2 with median 0 (range, −8 to 17) beats per minute. Mean HR decrease was not associated with transplantation type (biatrial versus bicaval, P = 0.2029) or with increasing duration of time from cardiac transplantation ( P = 0.0874). Conclusions: Although rare cases of cardiac arrest after NMB reversal have been reported, our experience would support the safety of neostigmine and glycopyrrolate in cardiac transplantation patients. Abstract : Although neuromuscular blockade reversal with neostigmine and glycopyrrolate has been reported to cause cardiac arrest as a rare complication in postcardiac transplant patients, the authors shows no serious cardiac complications and support the safety of neostigmine and glycopyrrolate in cardiac transplant patients.